Phytoplankton primary productivity in an urban eutrophic reservoir (São Paulo, Brazil) - Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo Luiz Martins (My University, 2008)
The aim of this study was to analyze temporal ..d vertical variation of the biomass and of phytoplankton primary productivity in an urban eutrophic reservoir, in relation to the physical and chemical characteristics of the water. The physical and chemical variables of the water were defined in the limnetic region of the reservoir, at depths of 0.0; 0.5; 1.0; 2.0; 3.0 and 4.0 meters. Three samples were taken to define both the physical and chemical variables, concomitantly with the biomass (chlorophyll-a and phaeophytin) and phytoplankton primary productivity (C-14 method). Based on data obtained on differences in depth of the mixture zone and the euphotic zone, it is hypothesised that, depending on the time of the year, phytoplankton is conditioned by differences in the light and nutrient regimes, which change according to the constant loads of nutrients thrown into the system. The highest concentration of chlorophyll-a in the photic zone of the limnetic region was observed in November 2000 (1,197.3 mg Chl L -1) and the lowest in November 1999 (94.0 mg ChI L -1), whereas the profiles of primary activity of phytoplankton presented the highest rates on the surface of the water column, with values varying from 84.7 (May 2000) to 1,376.7mg C m -3 h -1 (December 2000). Annual primary productivity was calculated at 1,567.0gC m -2y -1, considered euproductive. The primary productivity profiles reported in this study are typical of aquatic eutrophic systems, rich in plankton and with low light penetration. It can be stated that Garças Lake is a system that suffers from anthropogenic impact, through receiving large loads of organic pollution, reflecting on the physical and chemical characteristics of the water and on the high values of biomass and primary phytoplankton activity. © National Institute of Ecology, New Delhi.
Keywords: Anthropogenic impact; Garças lake; Tropical reservoir; anthropogenic effect; biomass; chlorophyll a; euphotic zone; eutrophic environment; hydrochemistry; organic pollutant; phytoplankton; primary production; reservoir; temporal analysis; urban area; vertical distribution; Brazil; Garcas Reservoir; Sao Paulo [Brazil]; South America